2020
DOI: 10.3390/jpm10020024
|View full text |Cite
|
Sign up to set email alerts
|

Neutral, Negative, or Negligible? Changes in Patient Perceptions of Disease Risk Following Receipt of a Negative Genomic Screening Result

Abstract: Most individuals who undergo genomic screening will receive negative results or results not sufficient to warrant a clinical response. Even though a majority of individuals receive negative results, little is known about how negative results may impact individuals’ perception of disease risk. Changes in risk perception (specifically reductions in perceived risk) may affect both probands and their family members if inaccurate information is communicated to family members. We surveyed patients who received negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Despite many questions study staff received from participants about their negative results when contacting participants to confirm receipt of results or invite participants to a related interview or survey study on receiving negative results, a very low proportion of participants utilized genetic counseling. This point is further emphasized by findings from a previous eMERGE III Network study (Stuttgen, Pacyna, Kullo, & Sharp, 2020) in which patient understanding of negative results returned was assessed, and data indicated that one third of participants were left with questions after receiving negative results. This suggests that merely providing a telephone number to access free genetic counseling services is not sufficient to provide support to individuals who have questions about their results.…”
Section: Discussionmentioning
confidence: 94%
“…Despite many questions study staff received from participants about their negative results when contacting participants to confirm receipt of results or invite participants to a related interview or survey study on receiving negative results, a very low proportion of participants utilized genetic counseling. This point is further emphasized by findings from a previous eMERGE III Network study (Stuttgen, Pacyna, Kullo, & Sharp, 2020) in which patient understanding of negative results returned was assessed, and data indicated that one third of participants were left with questions after receiving negative results. This suggests that merely providing a telephone number to access free genetic counseling services is not sufficient to provide support to individuals who have questions about their results.…”
Section: Discussionmentioning
confidence: 94%
“… 58 In addition, one site returned variants of uncertain significance (VUSs) for one disorder. Negative results were returned to participants at some sites, 64 , 65 , 66 and one site returned carrier status. 35 Sites also varied in whether they re-interpreted results over time in light of new information about clinical significance.…”
Section: Returning Results To Participants and Their Health Care Prov...mentioning
confidence: 99%
“…However, previous research indicates that negative results may be overinterpreted by participants as either providing more certainty of a true negative than the test can provide, also referred to as the ''nuanced negative,'' or potentially providing a false sense of hope and/or relief that a genetic disorder is not present. [22][23][24][25][26] Although the results report we provided to study participants with negative findings stated that ''no symptom-related results were found at this time,'' additional qualitative research is recommended to better understand how these findings are interpreted by clinicians and parents. For instance, it would be worthwhile to explore the degree to which clinicians emphasize the uncertainty of negative results, as well as the ways in which parents make meaning of negative results.…”
Section: Discussionmentioning
confidence: 97%